Increasing of Utility Properties of Grey Cast Iron Castings with Heat Treatment - Eperješi Š.; Malik J.; Vasková I.; Fecko D. (Archives of Foundry Engineering, 2015)
Grey cast iron belongs to materials for casting production, which have wide application for different industry branches. Wide spectrum of properties of these materials is given by the structure of base metal matrix, which can be influenced with heat treatment. Processes of annealing can be applied for grey cast iron without problems. During heat treatment processes, where higher cooling rates are used, the thermal and structural strains become important. Usage and conditions of such heat treatment for grey cast iron castings of common production are the subject of evaluation of this article.